2021
DOI: 10.1021/acscatal.0c05277
|View full text |Cite
|
Sign up to set email alerts
|

Combined Theoretical and Experimental Investigation of Lewis Acid-Carbonyl Interactions for Metathesis

Abstract: The coordination of a carbonyl to a Lewis acid represents the first step in a wide range of catalytic transformations. In many reactions it is necessary for the Lewis acid to discriminate between starting material and product, and as a result, how these structures behave in solution must be characterized. Herein, we report the application of computational modeling to calculate properties of the solution interactions of acetone and benzaldehyde with FeCl3. Using these chemical models, we can predict spectral fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Moreover, the adsorption site location of ASE is implemented only for certain surfaces, while more advanced surfaces would require manual definitions [179]. Owing to the general, atomistic nature of their core algorithm, the AFIR and GSM method, both Maeda et al [186][187][188] and Zimmerman et al [189][190][191][192][193][194][195][196][197][198][199] have studied homogeneous catalysis more extensively, also incorporating experimental information. Their algorithms can also be applied in a semiautomatic fashion by steering the exploration into certain branches of the reaction network, either by specifying specific internal coordination transformations or fragments of the molecules that shall be combined or dissociated.…”
Section: Computational Catalysis and Mechanism Explorationmentioning
confidence: 99%
“…Moreover, the adsorption site location of ASE is implemented only for certain surfaces, while more advanced surfaces would require manual definitions [179]. Owing to the general, atomistic nature of their core algorithm, the AFIR and GSM method, both Maeda et al [186][187][188] and Zimmerman et al [189][190][191][192][193][194][195][196][197][198][199] have studied homogeneous catalysis more extensively, also incorporating experimental information. Their algorithms can also be applied in a semiautomatic fashion by steering the exploration into certain branches of the reaction network, either by specifying specific internal coordination transformations or fragments of the molecules that shall be combined or dissociated.…”
Section: Computational Catalysis and Mechanism Explorationmentioning
confidence: 99%
“…Continuum solvation models such as SMx family, COSMO, and PCM can compute accurate solvation free energies thanks to sophisticated parameterization procedures and flexibility granted by a number of empirical parameters. [62][63][64][65][66][67][68][69] The solvation model density (SMD, one of SMx family) was used to represent the solvation effect in Dutra et al's 63 work studying the method of pK a calculation. The COSMO can reproduce comparable solvation effects with SMD, and was employed in Bamford et al's 69 work to determine the reaction pathway of B 2 (o-tolyl) 4 and boranes in computation.…”
Section: Continuum Solvation Modelsmentioning
confidence: 99%
“…We have previously demonstrated that FeCl 3 forms highly ligated complexes ( 6 ) in the presence of superstoichiometric amounts of acetone and benzaldehyde ( 2) : typical byproducts of carbonyl-olefin metathesis. , These byproducts decrease reaction rates and conversions via competitive interaction with the metal center or via production of a more sterically encumbered Lewis acid, decreasing the efficiency of the turnover-liming oxetane formation . Furthermore, work alongside Schindler and co-workers has shown that other Lewis bases present in the reaction mixture can inhibit reactivity, including those in the substrate .…”
Section: Introductionmentioning
confidence: 99%
“…This interaction typically involves the pairwise behavior succinctly described by Lewis: one donor and one acceptor . However, chemists continue to observe increasingly complex behavior when proceeding from the stoichiometric regime into catalysis, gaining evidence of 2:1, 3:1, and even 4:1 solution structures. , These in situ interactions need to be considered when exploring the mechanistic behavior of Lewis acid-catalyzed processes such as Diels–Alder reactions, aldol reactions, ene reactions, photochemical reactions, and more recently, carbonyl-olefin metathesis …”
Section: Introductionmentioning
confidence: 99%